KEPUASAN PESERTA PELATIHAN PENGAWAS OPERASIONAL PERTAMA PERTAMBANGAN TERHADAP KUALITAS PELAYANAN WIDYAISWARA DI PPSDM GEOMINERBA - Antonius Alex Harmoko (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2020)
Widyaiswara in carrying out their duties and functions must have the required competence in accordance with their field of specialization, as stated in the Regulation of the Head of State Administration Agency No. 5 of 2008 concerning Widyaiswara Competency Standards. This is to provide services to training participants. One of the service achievements can be measured by the level of satisfaction of the training participants with the services provided by widyaiswara. Based on the dimension of servant, in general the level of participant satisfaction with the widyaiswara services at The First Operational Supervisory (POP) of Mining Training was very satisfying with the perception of the training participants being in the range of 3.26-4.00. In this study, researchers measured the training participants satisfaction with widyaiswara services at POP Training at PPSDM Geominerba in 20 batches of 2018. Measurement of training participant satisfaction was carried out through a questionnaire with variables in the form of five dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy. From that, it is found that the tangible dimension is 3.29, the reliability dimension is 3.3, the responsiveness dimension is 3.31, the assurance dimension is 3.28, and the empathy dimension is 3.34.